2003
DOI: 10.1073/pnas.1332804100
|View full text |Cite
|
Sign up to set email alerts
|

ERK5 activation of MEF2-mediated gene expression plays a critical role in BDNF-promoted survival of developing but not mature cortical neurons

Abstract: Extracellular signal-regulated kinase 5 (ERK5) is a member of the mitogen-activated protein kinase family whose biological function in the CNS has not been defined. In contrast to ERK1 and ERK2, which are activated by neurotrophins (NTs), cAMP, and neuronal activity in cortical neurons, ERK5 is activated only by NTs. Here, we report that ERK5 expression is high in the brain during early embryonic development but declines as the brain matures to almost undetectable levels by postnatal day (P) 49. Interestingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
177
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(186 citation statements)
references
References 49 publications
7
177
0
2
Order By: Relevance
“…5A,B; Flavell et al 2006;Shalizi et al 2006). Furthermore, expression patterns of two known MEF2A activators, brain-derived neurotrophic factor (BDNF), which is linked to neuronal survival (Liu et al 2003;Shalizi et al 2003), as well as PPP3CB (also known as calcineurin A beta), which is involved in calcium influx-dependent dephosphorylation of MEF2A (McKinsey et al 2002;Shalizi et al 2006), showed human-specific delays consistent with the MEF2A expression profile and the average Figure 4. Regulation of human-specific expression patterns by TFs.…”
Section: Regulation Of Human-specific Expression Patternssupporting
confidence: 55%
“…5A,B; Flavell et al 2006;Shalizi et al 2006). Furthermore, expression patterns of two known MEF2A activators, brain-derived neurotrophic factor (BDNF), which is linked to neuronal survival (Liu et al 2003;Shalizi et al 2003), as well as PPP3CB (also known as calcineurin A beta), which is involved in calcium influx-dependent dephosphorylation of MEF2A (McKinsey et al 2002;Shalizi et al 2006), showed human-specific delays consistent with the MEF2A expression profile and the average Figure 4. Regulation of human-specific expression patterns by TFs.…”
Section: Regulation Of Human-specific Expression Patternssupporting
confidence: 55%
“…Activated ERK1/2 also phosphorylates FOXO3a, leading to the degradation and subsequent inhibition of FOXO3a [38]. ERK5, another member of the MAP kinases that is often pro-survival [39,40], is also a negative regulator of FOXO3a and fibroblasts from ERK5 and MEK5 null mice display increased FOXO3a activity [28]. JNK regulates FOXO3a nuclear translocation in breast cancer cells after paclitaxel treatment [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely expressed in many tissues, with the highest levels in the brain Yan et al, 2003). In neurons, ERK5 is activated by neurotrophins, including brain-derived neurotrophic factor (BDNF), neurotrophin (NT)-3, and NT-4 (Cavanaugh et al, 2001;Watson et al, 2001;Liu et al, 2003;Shalizi et al, 2003). A number of other extracellular stimuli, such as epidermal growth factor and G-protein-coupled receptors, also activate ERK5 (Kato et al, 1998;Marinissen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%